2013
DOI: 10.1007/s12185-013-1455-0
|View full text |Cite
|
Sign up to set email alerts
|

Deferasirox treatment improved hematopoiesis and led to complete remission in a patient with pure red cell aplasia

Abstract: A 64-year-old woman developed pure red cell aplasia (PRCA) 4 years after thymectomy for thymoma. During anti-thymocyte globulin treatment, the patient developed cytomegalovirus pneumonia and was thus unable to continue immunosuppressive therapy and became transfusion dependent. Deferasirox was started for treatment with iron overload when serum ferritin increased to >1000 ng/mL. Seven months after initiation of deferasirox treatment, serum ferritin level decreased the normal range and the patient has remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Hirokawa reported that treatment of post-transfusion iron overload may contribute to the improvement of the outcome of acquired PRCA [3]. Kojima reported that iron chelation therapy improved hematopoiesis and led to CR in one PRCA patient [22]. Our research is consistent with previous studies, confirms that iron overload is associated with poor prognosis of PRCA.…”
Section: Discussionsupporting
confidence: 91%
“…Hirokawa reported that treatment of post-transfusion iron overload may contribute to the improvement of the outcome of acquired PRCA [3]. Kojima reported that iron chelation therapy improved hematopoiesis and led to CR in one PRCA patient [22]. Our research is consistent with previous studies, confirms that iron overload is associated with poor prognosis of PRCA.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggest that management of infectious complications and treatment of post‐transfusion iron overload may contribute to the improvement of the treatment outcome of acquired chronic PRCA patients receiving immunosuppressive therapy. In fact, one report demonstrated that iron chelation therapy improved haematopoiesis in transfusion‐dependent patients with thymoma‐associated PRCA, although the mechanism was uncertain (Kojima et al , ). A similar effect of iron chelation therapy on haematopoiesis has been described in aplastic anaemia patients (Oliva et al , ; Lee et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems, therefore, that the increased iron concentration is the key modulator of hepcidin synthesis in this type of erythroid hypoplasia. In fact, it has been recently reported that the reduction of serum iron by iron chelation therapy promoted an improvement in erythropoiesis in PRCA, though the mechanism whereby this is achieved is still unclear [ 46 ].…”
Section: Discussionmentioning
confidence: 99%